Differentiation of endogenous erythropoietin and exogenous ESAs by Western blotting. Issue 11 (November 2020) - Yasuoka, Yukiko; Fukuyama, Takashi; Izumi, Yuichiro; Yamashita, Tetsuro; Nakayama, Yushi; Inoue, Hideki; Yanagita, Kengo; Oshima, Tomomi; Yamazaki, Taiga; Uematsu, Takayuki; Kobayashi, Noritada; Shimada, Yoshitaka; et al.
Abstract: Doping tests for the illegal use of erythropoiesis-stimulating agents (ESAs) have been developed. We developed a new Western blotting method to detect and distinguish endogenous erythropoietin (Epo, 35-38 kDa) and exogenous ESAs (epoetin α and β, 38-42 kDa; darbepoetin α, 47-50 kDa; epoetin β pegol, 93-110 kDa). Epo and ESAs are glycoproteins and deglycosylation using peptide-N-glycosidase F shifted all Epo and ESA bands except epoetin β pegol to 22 kDa. We cut the bands of Epo and ESAs from SDS-PAGE gels and analyzed them by Liquid Chromatography/Mass Spectrometry (LC/MS). LC/MS detected all endogenous Epo and exogenous ESAs as deglycosylated 22 kDa Epo, indicating that LC/MS analysis could confirm the presence of Epo or ESA, but could not distinguish between endogenous Epo and exogenous ESAs. We propose the following Epo doping tests: 1) detect Epo or ESAs by Western blotting of the glycosylated form; 2) increase the reliability by the band shift following deglycosylation; and 3) complete confirmation of Epo or ESA by LC/MS analysis using cut gels. One of the advantages of our method is that pre-purification of samples for Epo is not required in our Western blotting. Abstract : Biotechnology; Biochemistry; Molecular Biology; Public Health; Hematological System; Renal System; erythropoietin, erythropoiesis-stimulating agents, Western blotting, Liquid Chromatography/Mass Spectrometry analysis, doping, endogenous, exogenous.